Paying Positive to Go Negative: Advertisers' Competition and Media Reports - Andrea Blasco; Paolo Pin; Francesco Sobbrio (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
This paper analyzes a two-sided market for news where advertisers may pay a media outlet to conceal negative information about the quality of their own product (paying positive to avoid negative) and/or to disclose negative information about the quality of their competitors' products (paying positive to go negative). We show that whether or not advertisers have negative consequences on the accuracy of news reports ultimately depends on the extent of correlation among advertisers' products. Specifically, the lower is the correlation among the qualities of the advertisers' products, the (weakly) higher is the accuracy of the media outlet' reports. Moreover, when advertisers' products are correlated, a higher degree of competition in the market of the advertisers' products may decrease the accuracy of the media outlet's reports.
Keywords: L82; D82; 330